100 Facts: Flight - Sue Becklake & Miles Kelly
Which plane weighed less than its pilot? How many passengers can the Airbus A380 carry? Discover everything you need to know about flight in this extraordinary fact book. Flip through 100 fascinating facts covering everything from the earliest balloon flights to the age of the supersonic jet fighter, then test your knowledge with fun quizzes. Each page is packed with activities, projects and mind-blowing facts for a truly engaging experience. With stunning photographs and beautiful illustrations, this fun-filled book is sure to challenge young readers and prepare them for academic success.